Oxidizing pollutants can disrupt nestmate recognition in ants - Nan-Ji Jiang; Bhoomika Ashok Bhat; Eduardo Briceño-Aguilar; Angela Lehmann; Yuko Ulrich; Bill S. Hansson; Markus Knaden (Proceedings of the National Academy of Sciences, 2026)
Eusocial hymenoptera recognize nestmates based on colony-specific profiles of cuticular hydrocarbons (CHCs). While these profiles contain a variety of alkanes, the less abundant alkenes are crucial for nestmate recognition [F. R. Dani et al. , Chem. Senses 30 , 477–489 (2005)]. However, due to their carbon–carbon double bonds, alkenes can easily become degraded by oxidants. One of those oxidants, ozone, that usually reaches concentrations of 10 ppb in nonurban areas and ca 30 ppb in cities nowadays has been reported to often exceed 100 ppb in highly polluted regions, with levels above 200 ppb occasionally reported. Here, we show that short exposure to such elevated levels degrades alkenes in CHC profiles of all six investigated ant species and compromises nestmate recognition in five of them. Furthermore, a separate experiment with long-term exposure to such ozone levels corrupted brood care behavior within ant colonies, resulting in the death of larvae. The oxidizing pollutants like ozone have already been shown to corrupt interactions of flowers and their pollinators [B. Cook et al. , J. Chem. Biol. 46 , 987–996 (2020)] as well as sex pheromone communication in multiple species of flies [N. J. Jiang et al. , Nat. Commun. 14 (2023)]. Our data suggest that the detrimental effects of oxidant pollutants may be even more far-reaching by jeopardizing the functionality of eusocial colonies.